Implementation of Security on Library System Login Using a Combination of AES and RSA Cryptography - Siregar, M. Zaki Musaid (Journal of Technology and Computer, 2025)
The development of information technology has encouraged library systems to shift from manual methods to digital-based platforms. While this transformation improves efficiency, it also raises security risks in the login process, which handles sensitive user data. This research aims to implement login security using a combination of the Advanced Encryption Standard (AES) and Rivest-Shamir-Adleman (RSA) algorithms. AES-128 is used to encrypt passwords, while RSA is used to encrypt the AES output before transmission to the server. The research method includes requirements analysis, security architecture design, algorithm implementation, and testing through login simulations and traffic analysis using Wireshark. The results show that the combination of AES and RSA effectively protects user credentials and prevents unauthorized access to the transmitted data. The conclusion of this study is that the combined cryptographic approach provides dual protection for library system authentication. Further development is suggested by integrating secure communication protocols such as HTTPS and exploring modern public-key cryptographic algorithms.